Longitudinal Study on Health-Related Quality of Life in a Cohort of 96 Patients with Common Variable Immune Deficiencies - Tabolli, Stefano; Giannantoni, Patrizia; Pulvirenti, Federica; La Marra, Fabiola; Granata, Guido; Milito, Cinzia; Quinti, Isabella (Frontiers in Immunology, 2014)
Health Related Quality of Life in Common Variable Immunodeficiency Diseases evaluated by different tools were mainly used to compare different schedules of immunoglobulins administration in cross-sectional or short-term longitudinal studies. We assessed the health related quality of life and psychological status of CVID patients in a longitudinal study over a six years period by a generic, not disease-specific instrument (SF-36), and the risk of depression/anxiety by GHQ-12. At baseline, 96 patients were enrolled. After one year, a second assessment on 92 patients and after six years a third assessment on 66 patients were performed. Eighteen patients died during the study time. Health Related Quality of Life was low, with mental health scales less affected than physical scales. Worsening in SF-36 scales between the first and the third assessment was found for the physical functioning, body pain, general health, social functioning, role-emotional, scales. General Health scale showed a worse score in comparison to patients with other chronic diseases. We showed by GHQ-12 assessment that about one third of patients were at risk of anxiety/depression at all observation times, a figure that reached two third of patients only considering the group of females. Over the 6-years, 11/66 patients worsened their general health condition, passing from “GHQ-negative” to “GHQ-positive”, and worsened in SF-36 scales. A decrement of 1-point in each of physical functioning, vitality, social functioning and mental health scales increased the risk of developing anxiety/depression from 3 to 5 per cent. A negative variation of physical functioning increased the risk of psychological distress. In a survival analysis with dichotomized variables, physical functioning scores < 50 were associated with a RR of 4.4 and social functioning scores <37.5 with a RR of 10.0. In our study, the clinical condition and not the different treatment strategies with immunoglobulins had a major role on deter